Adaptation of The Multidimensional Depression Assessment Scale for Brazil (Research, Society and Development, 2023)
Major Depressive Disorder (MDD) affects about 5.8% of the Brazilian population, being the South American country with the highest number of cases. The diagnosis of MDD is performed through clinical assessment with the help of psychological instruments, however, many instruments measure depression in a unifactorial or bifactorial way. The Multidimensional Depression Assessment Scale (MDAS) seeks to assess MDD in four main domains, namely emotional, cognitive, somatic and interpersonal. This last domain isn’t frequently assessed by instruments for this diagnosis. However, its importance for depressed symptoms. The objective of the present study was to adapt the MDAS instrument to the Brazilian context. This is an adaptation study that followed the steps of translation, synthesis, evaluation by expert judges, evaluation by the target audience, back-translation, and evaluation by the original author of the instrument. The 52 items of the instrument went through all the processes and some underwent semantic and linguistic changes to adapt to the Brazilian culture. The Content Validity Coefficient (CVC) was performed and the instrument obtained a total CVC of 0.93 for clarity and 0.94 for relevance. The instrument adaptation process showed that the MDAS, in Brazilian Portuguese called the Escala Multidimensional de Avaliação da Depressão (EMAD), has a good semantic fit and is suitable for use in Brazil. EMAD presents a broader assessment of depression, which measures different dimensions, including interpersonal symptoms. This contributes to a more complete assessment and as a guide for psychological interventions in clinical practice.